Formal and Informal Long-Term Care and the Role of Family Carers: Czech Republic - Wija, Petr (European Journal of Mental Health, 2015)
Formal and Informal Long-Term Care and the Role of Family Carers: Czech Republic: The article discusses developments in long-term care and the availability of support for informal carers in the Czech Republic. Population forecast suggests that the process of demographic ageing in the Czech Republic will accelerate with the ageing of the baby boom cohorts of the 1940s and 1950s. Health and social policy has to address challenges of availability and quality of long-term care, and to develop support services to meet the needs of an ever growing number of older people and their families. The article analyses the long-term care system and the situation of family carers, and explores the challenges to be faced on the way to a more comprehensive long-term care system.